Integrating cross-border emergency medicine systems: Securing future preclinical medical workforce for remote medical services. Issue 1 (March 2018) - Ucinski, Tomasz; Dolata, Grzegorz; Hełminiak, Robert; Fischer, Lutz; Fleßa, Steffen; Brehmer, Bernhard; Viert, Armin; Grundmann, Volker; Rehberg, Sebastian; Krügel, Kathrin; Partecke, Maud; Brinkrolf, Peter; et al.
Abstract : The European Union intends to enable its citizens to interact across borders in relevant areas of society and culture to further integrate neighboring regions. Medicine has not been at the core of recent EU-funded efforts in central Europe, partially due to significant differences in health care administration, delivery, reimbursement, and culture. However, impeding changes in social structure and centralization of specialized care warrant changes in preclinical administration of medical care, which are already transforming practices across developed countries in central Europe. Moreover, demographic and social changes are transforming not only patients but also health care providers, thus leading to an increased need for specialized medical personnel, particularly in regions close to formerly secluding borders. The EU-funded cooperation project presented in this article is located in the Euroregion Pomerania, which consists of northeastern Germany and northwestern Poland. This project emerged because of the need to solve practical emergency medicine–related problems for many years, which brought partners together. Unfortunately, administrative and medical interaction has not become significantly easier with Poland joining the Schengen area in 2007 and, subsequently, initial international contracts regarding, among other things, emergency medicine being negotiated and signed thereafter. Three different interdependent areas of cooperation within the project deal with key aspects of an improved and eventually integrated cooperation. An accepted clarification of administrative and legal foundations – or the lack and thus the need thereof – needs to be defined. Specialized language and simulation-based education and practice sessions employing modern technology throughout will be introduced to the entire region. Finally, the pre-existing and developing acceptance and sustainability aspects of personnel involved in the aforementioned actions and stakeholders on both sides of the border will be evaluated. In essence, the project focuses on a multimodal improvement of professional cooperation of key providers of emergency medicine services in the Euroregion Pomerania. Thereby, it aims to improve infrastructure; interpersonal and professional skills of involved personnel, administrative, and cultural relations; and eventually identification of specialized personnel with their workplace and region to secure and retain important medical workforce in an otherwise remote area on both sides of a formerly secluded border.